ERROR ANALYSIS ON WORD STRESS OF 3rd SEMESTER STUDENTS OF ENGLISH STUDY PROGRAM OF FACULTY OF CULTURAL STUDIES - RINJANI, DITTA PUSPA AYU (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Error Analysis, Word Stress, Syllable, 3rdSemester Students. The students in the Faculty of Cultural Studies of Universitas Brawijaya are expected to speak English with correct pronunciation. It means that if there are many errors in speaking, the hearer will misunderstand. Therefore, the researcher conducts further observation in analyzing the word stress on English word uttered by the third semester students which have taken the Basic Oral and Auditory Skills (BOAS) class of English Study Program in Cultural Studies Universitas Brawijaya. The researcher applies the theory from Baker, (2012); Roach, (2000); Manipuspika,et al, (2012); and Oxford Dictionary, (1995). In order to find the results, the researcher finds problem of the study related with the study, it is to find out how the third semester students of English Study Program of Faculty of Cultural Studies pronounced two and three syllable words.The researcher uses qualitative research approach. Qualitative research relates with research design since the researcher tries to analyze the error on word stress in two syllables and three syllables words among third semester students of English Study Program of Faculty of Cultural Studies. The results show that the dominant error of two syllable - words is the word “create”, While, the dominant error in three - syllable words is the word ‘understand’. The word ‘understand’ is the most frequent error produced by the students which answer the problem of the study. Thus, it can be concluded that the three - syllable words is still difficult for the 3rd semester students of English Study Program of Faculty of Cultural Studies.The researcher suggests to the students of Cultural Studies Universitas Brawijaya to learn more about BOAS (Basic Oral and Auditory Skills) course since learning listening, reading and pronunciation comprehension are very important for the students of English Study Program. Therefore, it is expected for the students tohave the ability in identifying the stress in English word and have knowledge about the rules of the stress syllable.